Unravelling Factors Shaping Purchase Intention for “Tri” Cellular Card - Dewi Karina; Andi Oh; Zulfadli Hamzah (Yayasan Pendidikan Islam Al-Matani, 2023)
This study aims to investigate the factors that affecting purchase intention of Three products at Qmotion Shop in Pekanbaru . Factors examined in this study is the quality of the product, brand awareness, and promotion as an independent variable on purchase intentions as the dependent variable.The method used in sampling is a non probability method with accidental sampling techniques and the population is people who had bought and consumed Three products at Qmotion shop Pekanbaru. A total of 80 questionnaires, 80 questionnaires that can be used for statistical analysis using SPSS 16.0 program. The results of this study indicate that the variable of quality of the product, brand awareness, and promotion have positive significantly influence purchase intention.